Job seekers' perceptions about the PNet website as an E-recruitment tool within South Africa - Lesuthu, Kali (My University, 2013)
E-recruitment is one of the e-commerce applications that has enjoyed a multiple growth since its introduction in the early 1990s. There have been many variations regarding sophistication, types and success; as a result, this has posed a number of challenges to all stakeholders in these technologies. Thus, specific stakeholders may find specific applications suitable for their needs or within their reach to utilise. Companies can use these applications by implementing their own e-recruitment systems or by buying e-recruitment services provided by the third party, or a combination of both, depending on their objectives. The current study is focused on e-recruitment service providers who use general-purpose job boards that are fairly advanced in sophistication, such as the PNet recruitment website. These e-recruitment service providers are mostly recognised as online firms that manage their operations through their websites. However, behind these websites the physical ordinary businesses utilise the Internet as a means to perform their operations. Like other businesses, these e-recruitment service providers constantly face rapid shifts in technology, which places a considerable amount of pressure on them, as they persistently have to seek ways to stay ahead of their competitors. The competitiveness of every business lies in their knowledge of the market in which it operates in, as well the extent to which it is able to meet the needs of its customers. This study extends market knowledge and satisfaction of customers’ needs in the context of e-recruitment. It views the job seekers as the major customers for sustainability and competitiveness for e-recruiting companies or firms. The study was conducted using a survey method, sampling with n = 717 job seekers who use the PNet website to search for jobs. The primary data was obtained from the sample by means of a 6-point Likert questionnaire ranging from 1=strongly disagree to 6=strongly agree, measuring factors that influence the perceptions of job seekers regarding their use of the website. The questionnaire was administered via the Internet using the Sogo-Survey online tool. The main objective of the study was to evaluate job seekers’ perceptions about the PNet website as an e-recruitment tool, as well as to discover which factors are the best predictors of the continued use of the PNet website. The job seekers’ perceptions about the PNet website, as an e-recruitment tool in South Africa, were founded on the nine theoretical factors used in the questionnaire. From these factors, statistically significant differences in the factor means were present within the two independent groups, namely qualifications and gender. Using the standardised Beta value (β) the findings revealed that the attitude towards the website (.285) was the most important predictor, followed by information timeliness (.231), then attraction to the website (.182), usefulness of the website (.180) ease of use of the website (.170) and quality of website (.167). Findings and recommendations of this study are of importance to recruitment service providers and employers as it provides crucial information regarding their markets and how to improve the profitability of their businesses.
M. Tech. (Human Resource Management, Faculty of Management Sciences): Vaal University of Technology
Keywords: E-recruitment; E-commerce; PNet recruitment website; 658.311; Employee -- recruiting; Employee selection